Black and White Propaganda Triggering the War in Afghanistan - Evans, Martin Asta (Universitas Ahmad Dahlan, 2020)
Lone Survivor Film highlights on the American propaganda in Afghanistan war. In analyzing the topic, the writer has two objectives of the research. They are to analyze the American propaganda in Afghanistan war and to describe the situation of Afghanistan war as reflected in Lone Survivor film. This research is done under an interdisciplinary approach, as it applies American multidisciplinary studies. The writer uses descriptive qualitative method to analyze the data adopted from the scenes and dialogues of the film Lone Survivor. The result of this research is that propaganda in the film Lone Survivor can be classified into black and white propaganda. The black propaganda is shown as American pretends to have noble heart in some scenes in the film, in contrast with the truth that they have hidden agenda. Those are to change the audience’s view about America. The white propaganda in the film is shown when American tries showing to the world that there are some bad fact about Ahmad Shah group. Also there are some interesting situation between American soldiers and Taliban rebels which are found in Lone Survivor film.